Cross-cultural psychology : contemporary themes and perspectives - Keith, Kenneth D. (Kenneth Dwight), 1946- (Chichester, West Sussex, U.K. ; Malden, MA : Wiley-Blackwell, 2011)
"This book situates the essential areas of psychology within a cultural perspective, exploring the relationship of culture to psychological phenomena, from introduction and research foundations to clinical and social principles and applications. [bullet] Includes contributions from an experienced, international team of researchers and teachers [bullet] Brings together new perspectives and research findings with established psychological principles [bullet] Organized around key issues of contemporary cross-cultural psychology, including ethnocentrism, diversity, gender and sexuality and their role in research methods [bullet] Argues for the importance of culture as an integral component in the teaching of psychology"--
"Do people from different backgrounds experience basic psychological processes in the same way? Are there basic psychological principles that transcend culture? The articles in this volume, drawn from an experienced, international team of researchers and teachers, answer these questions and many others in order to situate the essential areas of psychology within a cultural perspective. Arranged thematically, this collection explores the relationship of culture to psychological phenomena. It covers foundational information about introductory and research topics, as well as more advanced clinical and social principles and applications. Packed with research findings and real-world examples, Cross-Cultural Psychology: Contemporary Themes and Perspectives discusses the importance of considering issues such as ethnocentrism, diversity, gender and sexuality in psychology and their impact on research methods"--
Part XI. Concluding Thoughts. -- 29. Cross-Cultural Psychology in Perspective: What Does the Future Hold? (Kenneth D. Keith).
Includes bibliographical references and index.
Keywords: Ethnopsychology -- Cross-cultural studies